2019
DOI: 10.1038/s41391-019-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

MEK-ERK signaling is a therapeutic target in metastatic castration resistant prostate cancer

Abstract: BackgroundMetastatic castration resistant prostate cancer (mCRPC) is incurable and progression after drugs that target the androgen receptor-signaling axis is inevitable. Thus, there is an urgent need to develop more effective treatments beyond hormonal manipulation. We sought to identify activated kinases in mCRPC as therapeutic targets for existing, approved agents, with the goal of identifying candidate drugs for rapid translation into proof of concept Phase II trials in mCRPC.MethodsTo identify evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…the decrease of pERK under rhCNTF stimulation, in normal prostate cellular model. Our data are in line with that of Nickols and colleagues 61 showing a correlation of prostate cancer recurrence with the increase of pERK expression levels. Moreover, the same authors demonstrated that the activation of ERK is characteristic of castration resistant prostate cancer while others found a correlation between increased ERK phosphorylation with both stage T and Gleason grade of prostate cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…the decrease of pERK under rhCNTF stimulation, in normal prostate cellular model. Our data are in line with that of Nickols and colleagues 61 showing a correlation of prostate cancer recurrence with the increase of pERK expression levels. Moreover, the same authors demonstrated that the activation of ERK is characteristic of castration resistant prostate cancer while others found a correlation between increased ERK phosphorylation with both stage T and Gleason grade of prostate cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the same authors demonstrated that the activation of ERK is characteristic of castration resistant prostate cancer while others found a correlation between increased ERK phosphorylation with both stage T and Gleason grade of prostate cancer. 61 , 62 So, we can hypothesize that inhibition of ERK phosphorylation can decrease migration and invasion processes downstream of this pathway. As a result, we can speculate that CNTF promotes epithelium homeostasis via pERK downregulation by an autocrine mechanism in normal prostate glandular basal compartment and that dysregulation of this mechanism could contribute to the onset of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from DDR, the most commonly impacted pathways were Phosphoinositide 3-kinase (PI3K, 7/13 (54%) cases), Mitogen-activated protein kinase (MAPK, 10 (77%) cases) and Wnt (9 (69%) cases) ( Table 2). PI3K and MAPK are intracellular and extracellular signalling pathways, respectively, that are key to the regulation of the cell cycle and, like certain DDR pathways, are therapeutically targetable (manipulable) with inhibitory drugs [30,31]. The Wnt signalling pathway is a cellular pathway involved in cell growth, embryogenesis and cell cycle progression, the activation of which has been implicated in progression to CRPC and treatment resistance [32].…”
Section: Shared Genomic Landscapementioning
confidence: 99%
“…Activation of the ERK pathway is associated with the development of numerous tumors [27]. MAPK/ERK pathway activation and subsequent interactions are highly regulated but may be out of regulation in cancer cells.…”
Section: Introductionmentioning
confidence: 99%